Do Personality Traits Affect Productivity? Evidence from the Lab - Maria Cubel; Ana Nuevo-Chiquero; Santiago Sanchez-Pages; Marian Vidal-Fernández (Institute for the Study of Labor (IZA), 2014)
While survey data supports a strong relationship between personality and labor market outcomes, the exact mechanisms behind this association remain unexplored. In this paper, we take advantage of a controlled laboratory set-up to test whether this relationship operates through productivity, and isolate this mechanism from other channels such as bargaining ability or self-selection into jobs. Using a gender neutral real-effort task, we analyse the impact of the Big Five personality traits on performance. We find that more neurotic subjects perform worse, and that more conscientious individuals perform better. These findings are in line with previous survey studies and suggest that at least part of the effect of personality on labor market outcomes operates through productivity. In addition, we find evidence that gender and university major affect the impact of the Big Five personality traits on performance.
Keywords: C91; D03; J3; M5; 330; Big-Five; personality traits; experiment; labour productivity; performance